Sex-Specific Patient Journeys in Early Parkinson's Disease in the Netherlands - Vlaanderen, Floris Pieter; de Man, Yvonne; Krijthe, Jesse H.; Tanke, Marit A. C.; Groenewoud, A. S.; Jeurissen, Patrick P. T.; Oertelt-Prigione, Sabine; Munneke, Marten; Bloem, Bastiaan R.; Meinders, Marjan J. (Frontiers in Neurology, 2019)
Abstract Objective To reconstruct a sex-specific patient journey for Dutch persons with Parkinson’s disease (PD) during the first five years after diagnosis. Method We analyzed a national administrative medical claims database containing data of all patients newly diagnosed with PD between 2012 and 2016 in the Netherlands. We performed time-to-event analysis to identify the moments when patients received care from neurologists, allied healthcare therapists or general practitioners. We also extracted relevant clinical milestones: unexpected hospitalization for PD, pneumonia, orthopedic injuries, nursing home admission and death. Using these data, we constructed the patient journey stratified for sex. Results We included claims data of 13,518 men and 8,775 women with newly diagnosed PD in the Netherlands. While we found little difference in neurologist consultations, women visited general practitioners and physiotherapists significantly earlier and more often (all p-values <0.001). After five years, 37.9% (n=3,326) of women had visited an occupational therapist and 18.5% (n=1,623) a speech & language therapist at least once. This was 33.1% (n=4,474) and 23.7% (n=3,204) for men. Approximately two years after diagnosis, PD-related complications (pneumonia, orthopedic injuries and PD-related hospitalization) occurred for the first time (women: 1.8 years; men: 2.3 years), and after five years, 72.9% (n=6,397) of women and 68.7% (n=9,287) of men had experienced at least one. Discussion Considering the strengths and limitations of our methods, our findings suggest that women experience complications and access most healthcare services sooner after diagnosis and more frequently than men. The identified sex differences extend the debate about phenotypical differences in PD between men and women.